Atuação do BNDES e parcerias com bancos privados: uma nova proposta - Araujo, Kamila Ferraz (2012)
Despite the growing share of private banks in lending, public banks, especially BNDES holds the lead in the total volume of operations. Although its performance has been modified over time, the operations are still concentrated in large companies. With the development of the Brazilian banking system, private institutions could partially replace these operations. The objective of this study is to propose a new form of partnership between BNDES and private banks. The proposal was based on the quality of banking institutions operating in the market and how the BNDES can reduce information asymmetry between borrower and lender. BNDES will participate analyzing the company and the operation by issuing a rating that would be used by private banks in decision making. With this partnership we expect increased competition in the banking sector and a reduction in BNDES participation in the credit market.